2023
DOI: 10.1039/d3ta03370h
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of amorphous polymers with high intrinsic thermal conductivity via automated physical feature engineering

Xiang Huang,
Shengluo Ma,
Yunwen Wu
et al.

Abstract: Informatics algorithm-driven approach overcomes the high-cost and time-consuming drawbacks of conventional trial-and-error procedures, and enables efficient exploration of polymers with desired properties. Intrinsically thermal conductive polymers are highly in demand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 85 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Averaged and centered Moreau-Broto autocorrelation of lag 8 weighted by intrinsic state [17] VE3_Dzs Logarithmic coefficient sum of the last eigenvector from Barysz matrix weighted by Sanderson EN [18] nHsOH The count of a specific atom-type Hydrogen (H) E-State associated with hydroxy groups (OH) [19] CIC1 1-ordered complementary information content [20] RotBFrac Fraction of rotatable bonds, excluding terminal bonds [21] Pharmaceuticals 2024, 17 The results of the Y-randomization test showed that none of the random trials could match the original model, as indicated in Table 1. The lesser values for R 2 and Q 2 on each iteration, and their averages (R 2 YS = 0.195 and Q 2 YS = −0.341) suggest that the developed QSAR models are not based on random correlations.…”
Section: Aatsc8smentioning
confidence: 99%
“…Averaged and centered Moreau-Broto autocorrelation of lag 8 weighted by intrinsic state [17] VE3_Dzs Logarithmic coefficient sum of the last eigenvector from Barysz matrix weighted by Sanderson EN [18] nHsOH The count of a specific atom-type Hydrogen (H) E-State associated with hydroxy groups (OH) [19] CIC1 1-ordered complementary information content [20] RotBFrac Fraction of rotatable bonds, excluding terminal bonds [21] Pharmaceuticals 2024, 17 The results of the Y-randomization test showed that none of the random trials could match the original model, as indicated in Table 1. The lesser values for R 2 and Q 2 on each iteration, and their averages (R 2 YS = 0.195 and Q 2 YS = −0.341) suggest that the developed QSAR models are not based on random correlations.…”
Section: Aatsc8smentioning
confidence: 99%